Aorto-Right Ventricular Tunnel in Transposition of the Great Arteries - Corno, Antonio F.; Durairaj, Saravanan; Anderson, Robert H. (Frontiers in Pediatrics, 2018)
Aorto-ventricular tunnel is an extremely rare congenital heart defect, consisting on failure of attachment of an aortic leaflet along the semilunar hinge. In all published reports the leaflet involved was either the right coronary leaflet, most frequently, or the left coronary leaflet, in most of the cases opening towards the left ventricle, with only one-eighth of the reported cases communicating with the right ventricle. Treatment of the aorto-ventricular tunnel has been anecdotally reported by interventional closure with a device and more frequently with surgical approach, either as an isolated malformation or with associated lesions. To the best of our knowledge, the presence of an aorto-ventricular tunnel of the non-adjacent aortic leaflet in transposition of the great arteries has never been reported. We have observed an aorto-ventricular tunnel involving the non-adjacent leaflet of the aortic root, which after arterial switch became the pulmonary root. The patient presented 18 years after the arterial switch with progressive dilatation of the right ventricle due to severe degree of pulmonary valve regurgitation, confirmed by echocardiography and cardiac MRI. Indication for surgery was given, with the plan for a pulmonary valve implantation. Because of the intra-operative finding of disconnection of the anterior leaflet of the pulmonary valve (former aortic valve) along the semilunar hinge, the surgical plan was modified an the anterior leaflet was attached to the valve annulus, with subsequent plasty in correspondence of the right and left commissurae to reduce the size of the dilated annulus to normal diameter. The post-operative course was uneventful, with extubation after few hours and discharge 4 days after surgery, with echocardiography showing trivial degree of pulmonary valve regurgitation. The patient remain in good conditions 6 months after surgery.